Caso de estudio: análisis y diagnóstico de una empresa del sector agroindustrial peruano, propuesta de un plan estratégico - Flores Aparicio, Patricia (2019)
The purpose of this research is to develop a strategic plan for a Peruvian company with international participation and with a solid position in the agribusiness and aquaculture sectors. To carry out this proposal, the current and future situation of the sector at national and international level will be analyzed, the internal and external context for the company will also be examined in order to obtain strengths, weaknesses, threats and opportunities. Subsequently, the strategic objectives will be redefined and along with it the business, corporate and functional strategies will be formulated to achieve the proposed goals. With respect to the strategic implementation of the plan, the redesign of the organizational structure will be considered and a control methodology will be aligned with a strategic map and an integrated scorecard. Finally, you will find the conclusions and recommendations that are based on the findings found in the company and the measures that must be used to achieve the strategic objectives of the plan. After executing this plan, the company will benefit from a greater positioning in the international market and with it an increase in its profitability that will benefit its stakeholders.